The influence of drying on the physiological quality of cape gooseberry (Physalis peruviana L.) fruits added with active components (2017)
ABSTRACT: Dehydrated products added with active components (AC) represent a healthy alternative for modern consumer. The aim of this research was to evaluate the influence of drying process conditions of cape gooseberry (Physalis peruviana L.) impregnated under vacuum with AC and dehydrated. A factorial design was performed with two independent variables, 2 levels per variable (temperature: 50 and 60ºC, air velocity: 2.0 and 3.0 m.s-1) and three replicates per drying condition. In fact, cape gooseberry fruits were previously impregnated under vacuum with an emulsion containing calcium and vitamins B9, C, D3 and E, which were subjected to dehydration until a water activity of approximately 0.6. In addition, drying rate curves presented in all cases two periods of decreasing speed. An increase of drying temperature decreases the processing time, presenting a greater AC degradation, while the air velocity offers a non-significant effect. The treatment which have allowed an AC better retention and low processing times was 60° C and 2 m.s-1, reaching levels of 204.8 ± 10.5 mg, 137.0 ± 34.7 μg, 13.6 ± 0.9 mg, 2.2± 0.6 μg, 7.0±1.2 mg for calcium and vitamins B9, C, D3 and E, respectively per 50 g serving of dehydrated cape gooseberry. An integration of the vacuum impregnation process with conventional air-drying, represents an effective technological alternative, which confers a higher added value to cape gooseberry fruit.